Konsep Pemerolehan Bahasa Arab Di Indonesia - Faisal, Faisal (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2022)
Language is a window to the world and an opening tool (key) of a science. It is said to be a window to the world because various knowledge and a thousand and one civilizations exist and are created because they are discussed. Language is a very important t hing for a human life. The purpose of this research is to examine the concept of Arabic language acquisition in Indonesia. The method used is to use literature review. The results of the analysis study show that there are striking differences between Behar iorism and Nativism in terms of language acquisition.